The Influence of Career Exposure and Soft Skills on Accounting Students' Career Interest through Self-Efficacy: Study on Accounting Students at Tadulako University - Farhan Zakhi Ramadan; Naila Salsabila; Aingjeli Natalia; Erwinsyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study examined the influence of career exposure and soft skills on students’ career interest in the accounting field, with self-efficacy acting as a mediating variable. Guided by career development theory, this research explored how access to professional information and the development of interpersonal competencies contribute to students’ confidence and motivation to pursue accounting careers. Using a quantitative approach, data were collected from 100 accounting students at Tadulako University through a structured questionnaire. The analysis, conducted using multiple regression and mediation testing, revealed that career exposure and soft skills significantly increased students’ self-efficacy, while self-efficacy had a strong positive effect on career interest. The findings highlight the importance of enhancing career-related exposure, strengthening soft-skills development, and fostering self-efficacy to support students’ readiness and motivation to enter the accounting profession.